2015
DOI: 10.1016/j.pedhc.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Directed Medical Play on Young Children's Pain and Distress During Burn Wound Care

Abstract: Directed medical play is used to reduce children's pain and distress during medical treatment. In this pilot study, young children who attended the burn clinic received either directed medical play provided by a child life specialist or standard preparation from the burn clinic nurse, to prepare for their first dressing change. Data were collected using validated instruments. Children who participated in medical play experienced less distress during their dressing change (M= 0.5, n=12) than those receiving sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 32 publications
3
67
0
Order By: Relevance
“…Music therapy reduced self-reported pain compared to standard care when provided immediately following CODs [58,59]; however, did not affect patients' self-reported pain when provided during CODs [58,59]. Likewise, 'medical play' prior to COD commencement did not affect patients' self-reported pain; however, did reduce nursing staff observations of pain and distress behaviour at insignificant levels [55]. In contrast, the use of Child Life Therapy (CLT) reduced patients' pain as observed by caregivers and an independent assessor; and increased nursing staff's observations of pre-procedural pain [49].…”
Section: Pain and Anxietymentioning
confidence: 84%
See 1 more Smart Citation
“…Music therapy reduced self-reported pain compared to standard care when provided immediately following CODs [58,59]; however, did not affect patients' self-reported pain when provided during CODs [58,59]. Likewise, 'medical play' prior to COD commencement did not affect patients' self-reported pain; however, did reduce nursing staff observations of pain and distress behaviour at insignificant levels [55]. In contrast, the use of Child Life Therapy (CLT) reduced patients' pain as observed by caregivers and an independent assessor; and increased nursing staff's observations of pre-procedural pain [49].…”
Section: Pain and Anxietymentioning
confidence: 84%
“…Therefore, its ability to meet the needs of First Nations people (respectfully used here in reference to Indigenous peoples globally) could not be ascertained [43]. Moore et al acknowledged the lack of cultural diversity within their study on medical play; however, this was brief and specific to the inclusion of African American and Hispanic families [55]. Similarly, Chester et al's study on hypnotherapy briefly acknowledged the lack of representation of Aboriginal and/or Torres Strait Islander children; however, did not elaborate on any potential implications or outline the ethnic/cultural diversity of included children [46].…”
Section: Cultural Componentsmentioning
confidence: 99%
“…If psychosocial outcomes were the metric, Child Life -the arts-based division that decreases distress, reduces pain perception as well as anesthetic need, and improves coping -would be far better funded. (Moore et al 2015) (Tyson et al 2014) (Durand 2015) I want all pediatric sub-specialists who order genetic testing, and their patients, to have access to genetic counseling. Relative Value Units (RVUs) are a complicated calculation method used by the Centers for Medicare and Medicaid Services (CMS) to determine physician compensation.…”
Section: The Big Picturementioning
confidence: 99%
“…3,6,7 Its use by the nurse in providing pediatric care is permeated by numerous benefits, not only for the child -who comes to comprehend better what is happening to her, becoming more calm, secure and collaborative -but also for the family, the nurse, the team and the care environment. 7 In the international literature, its use is highlighted as having a high therapeutic value for the child, contributing not only to physical improvement but also to the child's emotional well-being, 8 to reduction in pain and stress related to experiencing procedures such as venipuncture, 9 dressings, 10 inhalation therapies, 11 radiotherapy 12 and the preparation for surgery, 13,14 among others; it also has an effect on the reduction of the parents' anxiety, who come to understand this intervention's value. 15 Nevertheless, studies have not been identified related to the teaching of this strategy, it being the case that only one of these refers to the nurses' resistance regarding its use, due to their lack of familiarity with TP.…”
Section: Introductionmentioning
confidence: 99%